2013
DOI: 10.17221/337/2013-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of locality on content of phenolic compounds in white wines

Abstract: Lampíř L., Pavloušek P. (2013): Influence of locality on content of phenolic compounds in white wines. Czech J. Food Sci., 31: 619-626.Phenolic compounds in grapes and wines are significantly influenced by the environment. Phenolic compounds in grapes are therefore a good reflection of terroir. The authentic wines were made from seven white grape varieties and two localities in the Czech Republic. Sádek is a location on the edge of production wine-growing in the Czech Republic and Perná is a typical wine-growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…Each terroir is affected by climatic, geological, and soil factors, and also by human activity. Each grape produced in a specific terroir reflects the locality in its chemical composition (Lampíř & Pavloušek 2013). Phenolic compounds are divided into two main groups: nonflavonoids and flavonoids.…”
mentioning
confidence: 99%
“…Each terroir is affected by climatic, geological, and soil factors, and also by human activity. Each grape produced in a specific terroir reflects the locality in its chemical composition (Lampíř & Pavloušek 2013). Phenolic compounds are divided into two main groups: nonflavonoids and flavonoids.…”
mentioning
confidence: 99%
“…Similar to this study, Sen & Tokatli (2014) also reported that Muscat white wines could be distinguished from other white wines with a higher hydroxycinnamic acid content. Likewise in their research, Lampir & Pavlousek (2013) reported caftaric acid as the most dominant phenolic compound in Moravian Muscat wine (37 mg/L), followed by p-coutaric acid (14 mg/L). They also reported that the average content of these compounds was much lower in Perna, a site which is comprised of geological limestone bedrock (8 mg/L and 3 mg/L, respectively).…”
Section: Phenolic Compounds Of Muscat Of Bornova Winesmentioning
confidence: 78%
“…Gallic and protocatechuic acids normally range between 2.33 to 3.56 mg/L and 0.96 to 3.41 mg/L, respectively. Compared to Muscat of Bornova wines, Lampir & Pavlousek (2013) reported that gallic and protocatechuic acid concentrations were lower at 1.2 and 1.4 mg/L in Moravian Muscat wine, respectively. Catechin is one of the major flavan-3-ol monomers found in grapes and wines, and the concentration of catechin was found to be from 5.16 to 11.41 mg/L in Muscat of Bornova wines.…”
Section: Phenolic Compounds Of Muscat Of Bornova Winesmentioning
confidence: 85%
See 1 more Smart Citation
“…Kumšta et al (2012) analyzed 43 different Riesling wines from four vintages and 16 different localities in six sub-viticultural regions and reported that phenolic composition of the grapes and wines varied with the localities and the wines; wine regions were related to trans-resveratrol concentration. Lampíř and Pavloušek (2013) investigated the effects of regions on phenolic compounds of white wines produced from grapes grown in two different regions of Czech Republic and reported that protocatechuic acid, p-hydroxybenzoic acid, caftaric acid, cis-piceid, (+)catechin and (-)-epicatechin were significantly influenced by terroir.…”
Section: Individual Phenolic Compounds Of Winesmentioning
confidence: 99%